Emerging evidence of a silver lining: A ridge walk to avoid an economic catastrophe in Italy and Spain - Christopher Busch; Alexander Ludwig; Raül Santaeulàlia-Llopis (Leibniz Institute for Financial Research SAFE, 2020)
1. The coronavirus has led to a human tragedy, but it need not end up in an economic catastrophe. 2. In Southern Europe there are signs of a silver lining: the growth rate of the total number of deaths attributed to the coronavirus has been decreasing for weeks in Italy and Spain. 3. While the effect of the connement measures aim at limiting the spread of the virus is at best uncertain, the economic and social costs of a prolonged lockdown are much less ambiguous and potentially huge. Importantly, these costs can be very unequally distributed. 4. We argue that it is therefore time to start thinking about how to gradually unlock these countries, and we make some suggestions along this line starting with large-scale testing and continuous retesting as the most useful pre-condition.
Keywords: 330; Coronavirus; pandemic economics; lockdown costs